Effect of Institutionalisation on the Mental Health of Orphaned Adolescents - Dr. Aasia Maqbool, Dr. Lalit Mohan Sharma (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
The present investigation was undertaken to study and compare the mental health of institutionalized and non-institutionalized orphan adolescents. To collect quantitative data from 200 orphan adolescents, the English translated version of Mental Health Battery developed by Singh and Gupta was used. Qualitative data was collected through interviews of the teachers and caregivers. The quantitative data was analyzed by using Mean, SD and ttest; further, percentage analysis was used to analyse the qualitative data. The findings of the study revealed a significant difference between mental health of institutionalized and noninstitutionalized orphan adolescents and institutionalization has developed a feeling of alienation among the orphan children and thereby made them emotionally vulnerable. It was also revealed through qualitative data that emotional aloofness hinders the orphans to communicate their feelings, emotions and thoughts.